1993
DOI: 10.1101/gad.7.6.996
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of poly(A) site selection and trans-splicing in Leishmania.

Abstract: Intergenic regions of polycistronic pre-mRNAs of trypanosomatid protozoans are the sites of two processing reactions: polyadenylation of the upstream gene and trans-splicing of the capped miniexon to the downstream gene. Their close proximity and the lack of consensus motifs at poly(A) sites led us to test whether poly(A) site selection is governed by the location of the downstream splice acceptor in the DHFR-TS locus of Leishmania major. Whenever the position of the downstream splice site was altered, the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
244
1
18

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(274 citation statements)
references
References 47 publications
11
244
1
18
Order By: Relevance
“…One cleavage is associated with trans-splicing of a capped 39-nucleotide spliced leader sequence to the 5Ј-end of the mature mRNA (16). The second cleavage occurs in a region several hundred bases upstream of the splice acceptor site and is necessary for polyadenylation (17). The trans-splicing and polyadenylation reactions are tightly coupled and regulated by polypyrimidine tracts present within the intercistronic sequences (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One cleavage is associated with trans-splicing of a capped 39-nucleotide spliced leader sequence to the 5Ј-end of the mature mRNA (16). The second cleavage occurs in a region several hundred bases upstream of the splice acceptor site and is necessary for polyadenylation (17). The trans-splicing and polyadenylation reactions are tightly coupled and regulated by polypyrimidine tracts present within the intercistronic sequences (17).…”
mentioning
confidence: 99%
“…The second cleavage occurs in a region several hundred bases upstream of the splice acceptor site and is necessary for polyadenylation (17). The trans-splicing and polyadenylation reactions are tightly coupled and regulated by polypyrimidine tracts present within the intercistronic sequences (17). Numerous studies have shown that differential gene expression in Leishmania can be mediated by sequence elements in the 3Ј-UTRs 1 that affect mRNA stability (13, 18 -21).…”
mentioning
confidence: 99%
“…[37][38][39] In trypanosomes, so far only the polypyrimidine tract is known to affect trans splicing and polyadenylation of two adjacent genes. [12][13][14] Until recently no factor could be identified, which directly links the polyadenylation complex and the trans-spliceosome in trypanosomes. This is in line with our result that no known spliceosomal factor copurified with CPSF160.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a polypyrimidine tract upstream of a trans splice site affects polyadenylation of the upstream gene and trans splicing of the downstream gene. [12][13][14] Regulation of both individual RNA-processing reactions through a shared element may underline the close coupling of the two mechanisms. Recently, initial suggestive evidence of a physical linkage of the trans splicing and polyadenylation machineries was obtained, based on copurification of the polyadenylation factor CPSF73 with the spliceosomal U1 snRNP protein U1A.…”
Section: Introductionmentioning
confidence: 99%
“…For the time being no computational tool has been developed to accurately predict the site of polyadenylation in trypanosomatids, and only with the aid of experimental work can the complete information be extracted from their genes. The absence of canonic polyadenylation signal in trypanosomatids may be related to the mechanism that couples the polyadenylation of upstream gene to transsplicing of a downstream gene, and it has been shown that the modification of the downstream splice site (dinucleotide AG) shifted the poly (A) site (Lebowitz et al 1993, Mathews et al 1994. Nucleotide sequence per se does not inform precisely at which points the transcription of T. cruzi genes begins and finishes, but the existence of the cis elements (the dinucleotide AG, poly-pyrimidines rich tracts, adenine branching point) which are involved in the coupling of trans-splicing and polyadenylation provide the starting points for generation of transcription recognition algorithms (Gopal et al 2005, Benz et al 2005.…”
mentioning
confidence: 99%